2018
DOI: 10.1017/s0305000918000235
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in articulation rate and phonic groups during narration in French children aged four to eleven years

Abstract: This paper reports on an original study designed to investigate age-related change in the way French children produce speech during oral narrative, considering both prosodic parameters - speaking rate and duration of the prosodic speech unit - and linguistic structure. Eighty-five French children aged four to eleven years were asked to tell a story after they were shown an excerpt from an animated film. All their remarks were transcribed and coded using ELAN as an annotation tool. Each narrative was analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Outre la diversité de la valeur formelle et fonctionnelle du geste, le type de genre discursif fait aussi varier le recours aux différents types de gestes : en l'occurrence, les descriptions spatiales favorisent l'emploi de gestes déictiques ; l'explication s'accompagne souvent de gestes de structuration et la narration implique davantage le recours aux gestes représentationnels (Colletta et Pellenq, 2005). En ce qui concerne les récits, Colletta et al (2014) ont étudié les compétences narratives d'enfants à développement typique âgés de 3 à 11 ans. Les auteurs observent que les récits deviennent plus longs et se complexifient avec l'âge, les enfants de 10 et 11 ans produisant des récits plus complets et complexes que les enfants plus jeunes.…”
Section: L'usage Des Gestes Et La Construction Des Récitsunclassified
“…Outre la diversité de la valeur formelle et fonctionnelle du geste, le type de genre discursif fait aussi varier le recours aux différents types de gestes : en l'occurrence, les descriptions spatiales favorisent l'emploi de gestes déictiques ; l'explication s'accompagne souvent de gestes de structuration et la narration implique davantage le recours aux gestes représentationnels (Colletta et Pellenq, 2005). En ce qui concerne les récits, Colletta et al (2014) ont étudié les compétences narratives d'enfants à développement typique âgés de 3 à 11 ans. Les auteurs observent que les récits deviennent plus longs et se complexifient avec l'âge, les enfants de 10 et 11 ans produisant des récits plus complets et complexes que les enfants plus jeunes.…”
Section: L'usage Des Gestes Et La Construction Des Récitsunclassified
“…Colletta (2004) also demonstrated that multimodal story‐telling skills develop together and simultaneously. Colletta and Pellenq (2009) found an increase in all observed measures of explanations produced by French children aged 3–11 years old: duration, number of syllables, number of clauses, use of connectives as well as use of co‐speech gestures. Colletta (2009) demonstrated that children aged 9 years and over relied more on gesture and gaze resources and delivered truly embedded narratives, acting as narrators rather than only recounting facts and events they witnessed.…”
Section: Child Language As Variably Multimodalmentioning
confidence: 99%
“…Acquiring speech is a prerequisite for the education, training and development of children. Child communication development requires a purposeful and systematic work of teachers and parents, use specific educational tools and methods is the result of a combination of various components of mental development [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%